The Differential Diagnosis of Discrepant Thyroid Function Tests: Insistent Pitfalls and Updated Flow-Chart Based on a Long-Standing Experience - Campi, Irene; Covelli, Danila; Moran, Carla; Fugazzola, Laura; Cacciatore, Chiara; Orlandi, Fabio; Gallone, Gabriella; Chatterjee, Krishna; Beck-Peccoz, Paolo; Persani, Luca (Frontiers in Endocrinology, 2020)
Background: Discrepant thyroid function tests (TFTs) are typical of inappropriate secretion of TSH (IST), a rare entity encompassing TSH-secreting adenomas (TSHoma) and Resistance to Thyroid Hormone (RTHβ) due to THRB mutations. The differential diagnosis remains a clinical challenge in most of the cases. The objective of this study was to share our experience with patients presenting with discrepant TFTs outlining the main pitfalls in the differential diagnosis. Methods: medical records of 100 subjects with discrepant TFTs referred to Thyroid Endocrine Centers at the University of Milan were analyzed retrospectively. Patients were studied by dynamic testing (TRH test, T3-suppression test or a short course of long-acting somatostatin analog, when appropriate), THRB sequencing and pituitary imaging. Results: 88 patients were correctly diagnosed as RTHβ with (n=59; 16 men, 43 women) or without THRB variants (n=6; 2 men, 4 female) or TSHoma (n=23; 9 men, 14 women). We identified 14 representative subjects with an atypical presentation or who were misdiagnosed. Seven patients, with spurious hyperthyroxinaemia due to assays interference were erroneously classified as RTHβ (n=4) or TSHoma (n=3). Three patients with genuine TSHomas were classified as laboratory artefact (n=2) or RTHβ (n=1). Two TSHomas presented atypically due to coexistent primary thyroid diseases. In one RTHβ a drug-induced thyroid dysfunction was primarily assumed. These patients experienced a mean diagnostic delay of 27±13 months. Analysis of the investigations which can differentiate between TSHoma and RTHβ showed highest accuracy for the T3-suppression test (100% specificity with a cut-off of TSH <0.11 mUI/L). Pituitary MRI was negative in 6/26 TSHomas, while 11/45 RTHβ patients had small pituitary lesions, leading to unnecessary surgery in one case. Conclusions: Diagnostic delay and inappropriate treatments still occur in too many cases with discrepant TFTs suggestive of central hyperthyroidism. The insistent pitfalls lead to a significant waste of resources. We propose a revised flow-chart for the differential diagnosis.